الحماية القانونية للمرأة العاملة بالتشريعات المغاربية للعمل - طاوسي, فاطنة; شرون, حسينة (جامعة الوادي University of Eloued, 2019)
لقد شهد الإطار القانوني المحدد لمركز المرأة العاملة سواء على المستوى المغاربي أو الوطني تطورا كبيرا ابتداء من وعي المجتمع بأن المرأة عنصر فاعل في تطوير اقتصاد الدول حيث تجسد ذلك من خلال ضمان التشريعات العمالية المغاربية حقوقا تساوت فيها العاملة مع باقي فئات العمال كالأجر،الترقية، الراحة والعطل،الاستخدام والتدريب،الحق النقابي، الإضراب، الخدمات الاجتماعية وسلامة بيئة العمل، وفي ذات الوقت تميزت المرأة بحقوق تخصها دون باقي الفئات المهنية الأخرى كالحق في تخفيض ساعات العمل ببعض المهن، حظر العمل الليلي وممارسة الأعمال الخطرة والفصل بسبب الحمل،الحق في إجازة الأمومة بمقابل وساعات الإرضاع، وكل هذه الأحكام تؤكد حرص الدول المغاربية على حماية الفئات العمالية الضعيفة كالنساء. Abstract: The specific legal framework for the status of working women, whether at the Maghreb or national levels, has developed considerably from the society's awareness that women are active in the development of a country's economy. This is reflected in ensuring that Maghreb labor legislation has equal rights with other categories of workers such as wages, Holidays, employment and training, trade union right, strike, social services and safety of the work environment, At the same time, women were characterized by their rights without other occupational groups, such as the right to reduce working hours in certain occupations, the prohibition of night work, hazardous work and separation due to pregnancy, the right to maternity leave in return for hours of breastfeeding. All these provisions confirm the keenness of the Maghreb countries to protect vulnerable labor groups such as women.
legal Protection For Working Women In Maghreb Legislation Work
Keywords: الإجازة الأبوية ; إجازة الأمومة ; المساواة، المرأة العاملة، حماية الأجر ; العمل الليلي ; الأعمال الشاقة; Equality ; Wage protection ; Night work ; Maternity leave ; Parental leaveSerious business